IDDAH TALAK DAN HIKMAHNYA DITINJAU DARI PERSPEKTIF SYARIAT ISLAM: IDDAH TALAK DAN HIKMAHNYA DITINJAU DARI PERSPEKTIF SYARIAT ISLAM - muhmuhsin muhsin (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2022)
This research aims to find out a general picture of Iddah Talak and its lessons from the perspective of Islamic Sharia. In this paper, the author formulates several problems, namely: to what extent is the iddah talak wise from the perspective of Islamic Sharia and how does the iddah talak affect a marriage bond. To answer the problems mentioned above, the author uses a library research method, namely the author collects data by quoting expert opinions from reading books that are related to this discussion and opening internet sites as a complement. Meanwhile, in writing techniques, the author uses inductive, deductive and comparative methods. This research aims to determine the extent of the iddah talak and its wisdom from the perspective of Islamic Sharia.After the author has managed the existing data, the author can conclude that the iddah of divorce and its wisdom from the perspective of Islamic Sharia is to provide an answer to the response that a wife is not allowed to enter into a marriage with another man before the end of the iddah period due to her husband's divorce.